GUGATAN TENTANG PRAKTIK POLIGAMI OLEH PARTAI SOLIDARITAS INDONESIA (Study Analisis Dalam Perspektif Hukum Islam Dan Hukum Positif) - Nor Hidayatullah; Fathurrahman Alfa; Moh Murtadho (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Ths study aims to know the problem in lawsuit of Indonesian Solidarity Party (PSI) analysis about polygamy in positive law and islamic law perspective. This study focuses on 1) What is the point of view from Indonesian Solidarity Party (PSI) about polygamy and domestic violence?. 2) What is the point of view from Islamic law about polygamy and domestic violence?. This study is using qualitative approaching and the type of the study is case study. The data analysis collection is done by participatory observation, unstructured interviews, and documentation. The data analysis technique uses 3 steps from Miles and Huberman, namely data reduction, data display, and verification. To check the data validity, the researcher uses extending observation time, increasing preseverance, triangulating and checking the colleagues. The results of this study are, 1) The reason of Indonesian Solidarity Party (PSI) declines the polygami since they assumed that polygami same as domestic violence which involves pshycological distraction, physical violence, and social distraction, 2) In the National Regulation, it should be emphasized that regeneration and sexuality are not the one of the marriage purpose whereas there is a main of marriage purposes, that is affection, in order that the National Regulation of Marriage should be more dynamic, responsive, and high adaptability on the gender equality situation.Keyword: Poligamy, KDRT, Psi(Partai Solidaritas Indonesia), Hukum Positif, Hukumislam